DAMPAK PEMBANGUNAN BENDUNGAN LADONGI TERHADAP PRODUKTIVITAS USAHATANI PADI SAWAH DI KABUPATEN KOLAKA TIMUR - I Wayan Yogayana; Marsuki Iswandi; La Ode Alwi (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
This study aims to find out how much pepper productions is in Mowila District, Konawe Selatan Regency, and what factors influence pepper productions in Mowila District, Konawe Selatan Regency. The method used in this research is descriptive analysis and Cobb-Douglas analysis. The population and sample in this study were pepper farmers with 75 respondents taken from Mowila, Mataiwoi and Rakawuta villages. The determination of the sample was carried out using the Simple Random Sampling technique, with an error rate of 15% of the total population. The research results obtained showed that most of the age of pepper farmers ranged from 15-54 years, farming experience of more than 10 years, the education level of the majority of pepper farmers had high school education, the number of dependents was 1-4 people/head of family, the average land area (Ha) -The highest average of land used is 3 Ha and the lowest average of land used is 1 Ha, while the highest annual production rate reaches 1,500 kg and the lowest production level is 500 kg. The second research objective was analyzed using multiple linear regression with the help of SPSS version 23 software. The results showed that the highest pepper production in the villages of Mowila, Mataiwoi and Rakauta reached 1,500 kg/year and the lowest pepper production was 500 kg/year. Whereas the average pepper production in Mowila village is 961.8 kg/year, the average pepper production in Mataiwoi village is 921.4 kg/year and for the average pepper production in Rakauta village it reaches 1070.8 kg/year. Year. The factors that influence the production of pepper farming in Mowila Village, Mataiwoi Village and Rakawuta Village, Mowila District, South Konawe Regency which have a positive and significant influence are land area, farming experience, and pesticides, while those that are not significant in pepper production are fertilizer and labor.